INVESTIGATING THE EFFECT OF INTERNET BANKING QUALITY DURING AND AFTER THE PANDEMIC: A COMPARATIVE ANALYSIS - Nur Hayati; Wulan Lela Sari; Muji Rahayu (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2023)
This study aims to analyze the quality of Internet Banking services and their impact on customer satisfaction at State Owned Banks in Bandung before and after the COVID-19 pandemic. The seven independent variables used are response speed, data security, ease of use, user interface quality, accessibility, service availability, service quality, and information and communication technology, while the dependent variable is customer satisfaction. The survey method was used to collect data from 100 respondents who are customers of State-Owned Banks in Bandung. Multiple regression analysis was carried out to determine the relationship between the independent variable and the dependent variable accompanied by a different test. The results showed that Internet Banking Service Quality during and after the Covid 19 Pandemic period had a positive and significant effect simultaneously, while partially only the Service Quality and Information and Communication Technology variables had a positive and significant effect during and after Covid 19, while other variables had a positive effect but not significant. In addition, this study also concluded that there was a decrease in the Information and Communication Technology and Service Quality variables after the pandemic compared to during the pandemic from customer perceptions. The implication is that in the New Normal era, apart from the two dominant aspects mentioned above, there are indications that State Owned Bank is trying to improve its service quality through other variables to increase customer satisfaction.